2016
DOI: 10.1001/jamafacial.2015.1944
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postrhinoplasty Taping on Postoperative Edema and Nasal Draping

Abstract: BACKGROUND Edema persists for months after rhinoplasty. Numerous modalities have been described to counteract postoperative edema. OBJECTIVE To evaluate the effect of postrhinoplasty taping (PRT) on nasal edema and nasal draping. DESIGN, SETTING, AND PARTICIPANTS In this randomized clinical trial, 57 patients undergoing rhinoplasty at a tertiary reference center from August 1, 2014, to January 31, 2015, were assigned to a control group or to 2-or 4-week PRT groups. Baseline nasal thickness was measured with ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 28 publications
2
46
0
Order By: Relevance
“…Farahvash et al studied the effects of applying strips of different lengths to cover the lower eyelid of one side and the malar area of the same patient on ecchymosis, and demonstrated that covering the lower eyelid and whole malar area reduced ecchymosis (12). Ozucer et al indicated that keeping the strips on the nasal dorsum after removing the splint reduced edema on the nasal dorsum, and reported that this was associated with the pressure of the nasal strip (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farahvash et al studied the effects of applying strips of different lengths to cover the lower eyelid of one side and the malar area of the same patient on ecchymosis, and demonstrated that covering the lower eyelid and whole malar area reduced ecchymosis (12). Ozucer et al indicated that keeping the strips on the nasal dorsum after removing the splint reduced edema on the nasal dorsum, and reported that this was associated with the pressure of the nasal strip (13).…”
Section: Discussionmentioning
confidence: 99%
“…Various methods have been used to reduce edema and ecchymosis, including types of osteotomies, open or closed rhinoplasty techniques, steroids, and use of decongestants (6)(7)(8)(9)(10). In addition to applying strips to the nasal dorsum following rhinoplasty using different techniques and at different times, procedures are performed with different techniques on the periorbital area to reduce edema and ecchymosis (11)(12)(13). The objective of this study was to assess the efficacy of applying adhesive strips on the periorbital area following rhinoplasty to reduce postoperative edema and ecchymosis in the early and late periods.…”
Section: Introductionmentioning
confidence: 99%
“…In certain patient populations with thick skin, other measures may be needed to address the prominent supratip scar, including the use of 0.1 mL of 10 mg/mL triamcinolone injections spaced out 4 to 6 weeks apart, direct excision of fat and the superficial musculoaponeurotic system in the supratip, or the use of tacking sutures to obliterate supratip dead space and more aggressive taping measures. [34][35][36][37] Last, loss of tip projection can lead to the anterior septal angle protruding forward as described earlier, and tip projection correction methods will be discussed separately.…”
Section: Pollybeak Deformitymentioning
confidence: 99%
“…8 Other strategies for dealing with a thick soft-tissue envelope are preoperative treatment with isotretinoin, intraoperative excision of fat and superficial musculo-aponeurotic system (SMAS) in the supratip, placement of a tacking suture to better appose the skin to the cartilage, postoperative injection of steroids, and postoperative taping. [9][10][11]…”
Section: Cartilaginous Dorsum Pollybeakmentioning
confidence: 99%